Impact of Brand Awareness and Brand Image, Perceptions of Quality on Purchasing Decisions - Faruq Syah Permana Putra; Nurul Qomariah; Dwi Cahyono (Universitas Muhammadiyah Jember, 2021)
This study aims to determine and analyze the impact of brand awareness and brand image on quality perceptions and purchasing decisions of Philips lamps in Bondowoso Regency. The population in this study are all people who have used or purchased Philips lamps in the period 2018 to 2019. The number of research respondents was 100 people. Data analysis techniques used structural equation modeling (SEM) with Warp PLS 5.0 software. The results showed that the fit and quality indices model showed that the value of Average Path Coefficient (APC) = 0.375 and P 0.001 Average R-squared (ARS) = 0.685, and P 0.001 Average adjusted R-squared (AARS) = 0.678, P 0.001 Average block VIF (AVIF) = 1.688, it means that this research model is considered feasible and statistically acceptable because the p value is less than 0.05. The R-squared contribution ratio (RSCR) = 1,000 means it is classified as a statistically ideal regression value. The results of PLS calculations in this study produce the coefficient of brand awareness variables β = 0.26 with a p value 0.01. The coefficient of brand image variable is β = 0.54 with p value 0.01. The coefficient of brand awareness variable β = 0.34 with p value 0.01. The coefficient of the brand image variable is β = 0.2 with a value of p = 0.03. The coefficient for the perceived quality variable is β = 0.53 with a p value 0.01. The results of the path analysis calculation show that brand awareness has an effect on perceived quality, brand image on perceived quality, brand awareness on purchasing decisions, brand image on perceived purchasing decisions, the influence of perceived quality on purchasing decisions.